Use of a recombinase polymerase amplification commercial kit for rapid visual detection of Pasteurella multocida - Zhao, Guimin (BMC Vet Res, 2019)
BACKGROUND: Pasteurella multocida (P. multocida) is a bacterium that causes bovine respiratory disease (BRD) and haemorrhagic septicaemia (HS) in cattle, buffaloes and bison. Rapid point-of-care diagnosis or regular testing of Pasteurellosis, therefore, could contribute greatly to early detection, and screening infected animal is important. Up to now, there are no published reports on the use of recombinase polymerase amplification (RPA) combined with a lateral flow dipstick (LFD) for P. multocida detection. RESULTS: This study proposes a promising isothermal detection method for P. multocida with the potential to be developed as an on-site test for Pasteurellosis. The method includes an RPA combined with LFD. First, the analytical sensitivity and specificity of P. multocida RPA-LFD were tested. The RPA-LFD, performed at 39 °C, successfully detected P. multocida DNA in 30 min, with a detection limit of up to 120 copies per reaction. Then, the practicability of RPA-LFD was analysed using 62 nasal swabs and 33 fresh lungs samples from 17 different dairy farms. Compared to real-time quantitative PCR (qPCR), the RPA-LFD assay yielded a clinical specificity of 95.15%, positive predictive value (PPV) of 95.15% and 0.958 kappa coefficient. Compared with the culture method, it achieved 100% sensitivity, 67.20% specificity and a 0.572 kappa coefficient. CONCLUSIONS: These results combined with the simple conditions required for the performance of the RPA-LFD assay, have demonstrated the effectiveness and practicability of the method for development into a regular on-site protocol for the diagnosis of Pasteurellosis.